Reuse of hospital bedpans - Tamires Alessandra Mineli; Denise de Andrade; Simone de Godoy; Isabel Amélia Costa Mendes; Silvia Helena Tognoli; Leila Maria Marchi-Alves (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to evaluate the results of two methods of hospital bedpan reprocessing. Methods: cross-sectional study. Hospital bedpans containing a biological material contamination simulator or organic matter were submitted to manual cleaning followed by disinfection with 70% alcohol solution or thermodisinfection. Permanence of simulated contamination was evaluated by using the fluorescence technique and presence of organic matter was verified by carrying out the protein detection test. Results: the contamination simulator was found in bedpans submitted to both processes. The seat was dirtier after manual cleaning (p=0.044) in comparison with the result obtained with thermodisinfection. Automatized decontamination led to worse results when compared to the manual procedure for the scoop and external bottom (p=0.000). The protein detection test was positive in two items after thermodisinfection. Conclusions: manual cleaning followed by rubbing with 70% alcohol solution proved more effective than automatized cleaning in the reprocessing of hospital bedpans. There are relevant issues regarding reuse of hospital bedpans.